A practical scheduling algorithm to achieve 100% throughput in input-queued switches - Mekkittikul, A.; McKeown, N. (Annual Joint Conference of the IEEE Computer and Communications Societies, 1998)
Input queueing is becoming increasingly used for high-bandwidth switches and routers. In previous work, it was proved that it is possible to achieve 100% throughput for input-queued switches using a combination of virtual output queueing and a scheduling algorithm called LQF However, this is only a theoretical result: LQF is too complex to implement in hardware. We introduce a new algorithm called longest port first (LPF), which is designed to overcome the complexity problems of LQF, and can be implemented in hardware at high speed. By giving preferential service based on queue lengths, we prove that LPF can achieve 100% throughput.